2010
DOI: 10.1007/s10802-010-9389-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Girls’ and Boys’ Delinquency and Associated Problems

Abstract: Developmental trajectories in delinquency through adolescence were studied along with family and peer relationship problems. Drawing from eight waves of data over seven years, we conducted trajectory analyses with a sample of 746 students (402 girls; 344 boys). Analyzing girls and boys together, a five-class model emerged: 60% of the adolescents rarely reported delinquency; 27.7% reported low initial levels with moderate levels of delinquency over time; 6% in the late onset group reported initially low and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
5
33
1
Order By: Relevance
“…Delinquent behavior increased with age; however, the increase was less steep for older youth. As mentioned earlier, there is a trajectory of delinquent behavior that peaks in late adolescence and then begins to decline in early adulthood (Maldonado-Molina et al, 2009;Pepler et al, 2010). Given that the occurrence of delinquent behavior in this study was beginning to occur less often among older youth, perhaps, a similar pattern would have been evidenced if the youth had been followed into adulthood.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Delinquent behavior increased with age; however, the increase was less steep for older youth. As mentioned earlier, there is a trajectory of delinquent behavior that peaks in late adolescence and then begins to decline in early adulthood (Maldonado-Molina et al, 2009;Pepler et al, 2010). Given that the occurrence of delinquent behavior in this study was beginning to occur less often among older youth, perhaps, a similar pattern would have been evidenced if the youth had been followed into adulthood.…”
Section: Discussionsupporting
confidence: 56%
“…This could be due to a number of factors. Studies that have investigated trajectories of delinquent and antisocial behavior have identified a group of youth for whom delinquency peaks and then begins to decline (Fergusson & Horwood, 2002;Moffitt, 1993;Pepler, Jiang, Craig, & Connolly, 2010). It is possible that the decrease in delinquency seen in our study reflects youth who fit this pattern.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, the differences in findings may relate to methodological differences across studies. One difference pertains to how risk behavior has been measured across studies, such that different scales have been used and varying domains of risk behavior have been assessed (Gutman & Eccles, 2007; Measelle et al, 2006; Pepler et al, 2010). For example, in contrast to Gutman, Eccles, Pepler, and colleagues, the risk behavior scale used in the current study and the study by Measelle and colleagues included substance use in addition to delinquent and antisocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examine whether the composition of adolescent social networks-and in particular, the extent to which members of these networks engage in greater frequency/quantity of substance use-is associated with individual-level substance use in sexual minority youths. Based on previous research (Hatzenbuehler et al, 2012;Ueno, 2005), we hypothesized that sexual minority adolescents' social isolation and rejection from central social networks places them in marginalized or "deviant" peer networks in which substance use is common and more acceptable (Fergusson et al, 2002;Moffi tt, 1993;Monahan et al, 2009;Pepler et al, 2010).…”
mentioning
confidence: 99%